Cannabis Use and Associated Harms among Schizophrenia Patients in a Nigerian Clinical Setting: A Case–Control Study - Lasebikan, Victor; Aremu, Olaolu O. (Frontiers in Psychiatry, 2016)
Aim: The overall aim of this study was to determine the prevalence of cannabis use among patients with schizophrenia with associated levels of harm in a Nigerian clinical setting. Method: In this case-control study, consecutive 150 patients with schizophrenia were matched by age and gender with an equal number of patients that utilized the general outpatient department of the State Hospital, Ring Road Ibadan. The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) was used to obtain prevalence of cannabis use and level of health risk as determined by the ASSIST score. The Positive and Negative Syndrome Scale (PANSS) was used to determine the severity of psychosis. Results: Prevalence of cannabis use among the cases was 10.0% and 2.7% among the control group, p = 0.03. Mean ASSIST score was significantly higher among the cases compared with the control, p < 0.001. Respondents of male gender and those who were not married were significantly more likely to be cannabis users among patients with schizophrenia, p < 0.001, p < 0.02 respectively. Conclusion: Cannabis use was prevalent among patients with schizophrenia and was associated with health risks. Thus, routine screening for cannabis use and brief intervention is suggested to be integrated into care for adolescents and adults with schizophrenia.